A Golden Treasure from Korea: The Gilt-Bronze Bodhisattva Statue of Silla - Young-ae Lim (Religions, 2022)
A gilt-bronze statue of a standing bodhisattva was discovered at the Sŏllimwŏn Temple site. The statue is notable as its halo and pedestal were found intact at the time of discovery, and the bodhisattva figure itself is almost perfectly preserved. There are only a few instances of gilt-bronze statues from the Unified Silla kingdom that can be definitively linked to the site of their original placement. Sŏllimwŏn was physically distant from the royal palace, but its status as a central temple of the Sŏn School 禪宗 and the activities of pre-eminent monks in the ninth century made it important enough to become the site for a splendid gilt-bronze bodhisattva statue. Based on physical, stylistic, and scientific evidence, the statue dates to the latter half of the ninth century and has ties to the Buddhist monk Master Honggak 弘覺禪師. A unique example of a gilt-bronze sculpture, the Sŏllimwŏn bodhisattva is a valuable part of Buddhist material culture in Korea.